Link prediction method based on matching degree of resource transmission for complex network - Shuxin LIU; Xing LI; Hongchang CHEN; Kai WANG (Tongxin xuebao)
In order to solve the problem that many existing resource-transmission-based methods ignore the important influence of the matching degree of two endpoints on resource transmission,a link prediction method was proposed based on matching degree of resource transmission for complex networks.Firstly,by analyzing the two endpoints on the resource transmission path in detail,the method of quantifying the matching degree between two nodes was proposed.Then,in order to describe the influence of matching degree on resource transmission process between nodes,the matching degree of resource transmission was defined.Finally,based on the matching degree of resource transmission,a resource transmission matching index was proposed considering the resource amount of bidirectional transmission between nodes.The experimental results of nine datasets show that compared with other similarity indices,the proposed index can achieve higher prediction accuracy under the AUC and Precision metrics.